Breath-taking Pedagogy: Self-care & Ethical Pedagogy in the Climate of Anti-Blackness and COVID-19 - Jones, Shermaine M. (Radical Teacher, 2022)
As a Black literary scholar working and living at the intersection of the urgent matters of the COVID-19 pandemic and national racial unrest, I felt a sense of despondency and disillusionment about the kind of work I could and should be doing and what its impact would be. Racial fatigue weighed heavily on my mind and spirit. I questioned, how does literature help us to better understand the concerns of our moment and imagine a more equitable future? What does ethical and engaged pedagogy look like in this moment? “Breath-taking Pedagogy” examines my concerns and anxieties while navigating these coinciding threats to Black breath and the ways this experience informed a radical shift in my approach to teaching and public scholarship. Specifically, I detail how I have tried to reconcile my role and contribution through community engaged scholarship that demonstrates the transformative potential of literature and through an ethical teaching practice that privileges equity, empathy, and self-care.